Efficacy and safety of Keluoxin capsule in combination with Western medicine for diabetic kidney disease: A systematic review and meta-analysis - Zhang, Wenhua; Zhou, Jingxin; Wang, Churan; Wang, Xu; Zhang, Shuwen; Jia, Weiyu; Jiang, Yijia; Lin, Lan; Gong, Yanbing (Frontiers in Pharmacology, 2023)
Objective: Keluoxin capsule (KLXC) has been widely used in diabetic kidney disease (DKD), but its efficacy and safety have not yet been clarified. A systematic review and meta-analysis were performed to assess the efficacy and safety of KLXC for DKD. Methods: The randomized control trials (RCTs) included KLXC searched from seven major English and Chinese databases up until 3 June 2022. The methodological quality and risk of bias were assessed by version 2 of the Cochrane risk-of-bias tool (RoB 2) for the RCTs from the Cochrane Handbook. The analyses were conducted by RevMan 5.4 and Stata 17.0. Results: A total of 20 trials with 1,500 participants were identified. The meta-analysis showed that KLXC combined with Western medicine was superior to the use of Western medicine alone for DKD which included improvements in the estimated glomerular filtration rate (eGFR) [MD = 3.04, 95% CI (0.30, 5.78), p = 0.03], reduction in microalbuminuria (mALB) [MD = −25.83, 95% CI (−41.20, −10.47), p = 0.001], urinary albumin excretion rate (UAER) [SMD = −0.97, 95% CI (−1.50, −0.44), p = 0.0003], 24-h urine protein (24hUpro) [SMD = −1.31, 95% CI (−1.82, −0.80), p < 0.00001], serum creatinine (Scr) [MD = −11.39, 95% CI (−18.76, −4.02), p = 0.002], blood urea nitrogen (BUN) [MD = −1.28, 95% CI (−1.67, −0.88), p < 0.00001], fasting blood glucose (FBG) [MD = −0.51, 95% CI (−0.90, −0.11), p = 0.01], total cholesterol (TC) [MD = −1.04, 95% CI (−1.40, −0.68), p < 0.00001], triglycerides (TG) [MD = −0.36, 95% CI (−0.50, −0.23), p < 0.00001], and low-density lipoprotein cholesterol (LDL) [MD = −0.39, 95% CI (−0.71, −0.07), p = 0.02]. Results showed no statistically significant difference in glycated hemoglobin (HbA1c) (p = 0.14) or adverse events (p = 0.81) between the two groups. Conclusion: The combination of KLXC and Western medicine had a positive effect on DKD. However, due to the high clinical heterogeneity and low quality of included studies, further standardized, large-scale, rigorously designed RCTs for DKD in the definitive stage are still necessary to achieve more accurate results. Systematic Review Registration:https://inplasy.com/inplasy-2021-11-0067/, identifier INPLASY 2021110067.